Empowering Children's Education through Tutoring Programs: Community Service in Medalem Village, Sidoarjo: Pemberdayaan Pendidikan Anak melalui Program Bimbingan Belajar: Pengabdian Kepada Masyarakat di Desa Medalem, Sidoarjo - Manik Ayu Titisari; Nabillah Nur Khoirotun Nissa; Revina Ayu Pradyta; Nur Asiyah; Heru Adjie Sasongko; Muhammad Adit Dwiky (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The tutoring program conducted in Medalem Village, Sidoarjo, aimed to improve the motivation and interest in learning among elementary school students, which had declined due to the COVID-19 pandemic. Through a personalized approach with intensive assistance in Mathematics and Indonesian language subjects, the program successfully increased student engagement, with attendance rising from 15 participants in the first week to 25 participants in the final week. Additionally, active involvement of parents in the home learning process contributed to the program's success. Qualitative evaluation revealed a significant increase in students' learning motivation. Many students who were previously passive became more confident and enthusiastic about their studies. This program demonstrated that tutoring tailored to the needs of students can effectively address the decline in learning motivation. The program recommends greater involvement from schools and the use of digital technology to sustain the program in the future. The findings suggest that a personalized and collaborative tutoring approach can serve as an effective solution to improving the quality of education in local communities.